Local experiences of connectivity and mobility in the ancient west-central Mediterranean (Sheffield, South Yorkshire ; Bristol, CT)
xiii, 353 sayfa
Keywords: “Local Experiences of Connectivity and Mobility in the Ancient West-Central Mediterranean brings together a series of papers that explore theoretical and material approaches to connectivity and mobility in the ancient Central and Western Mediterranean. The diverse contributions span the period of the Late Bronze Age through the Late Roman period and focus on locales across the central-western Mediterranean region, specifically Iberia, Southern France, North Africa, Italy, Sicily, the Balearic Islands, Sardinia, and Corsica. Case studies are grouped around the themes of people, things, and landscapes. Focusing on the small-scale picture, they illuminate local experiences of connectivity and mobility that run “against the grain” of more usual large-scale narratives of Greek, Phoenician, Carthaginian, and Roman contact and colonization in the west. Taken together, the chapters demonstrate the value of dialogue across regional and national divides that have traditionally fragmented research in these regions. Further, they bring out the common themes that emerge when approaching connectivity and mobility from a broad diachronic perspective when not confined by traditional divisions between prehistory and the classical period. The book highlights the work of emerging scholars, framed by discussions by prominent scholars in the field, combining deep expertise with fresh perspectives and new approaches to connectivity and mobility in the ancient world“ --